Sorption and pore condensation behavior of pure fluids in mesoporous MCM-48 silica, MCM-41 silica and controlled pore glass. - Thommes, Matthias; et al. (Studies in Surface Science and Catalysis, 2001)
The authors present a systematic study on the sorption and pore condensation behavior of nitrogen and argon in various silica materials (MCM-48, MCM-41 and Controlled Pore Glass (CPG)) at 87 and 77 K. A detailed characterization with respect to surface area, pore vol. and pore size distribution together with a detailed comparison of sorption isotherms in MCM-48 and MCM-41 silica materials of nearly equal pore size was performed. The results show clearly that the shape of sorption isotherms (in particular the shape and the width of sorption hysteresis loops) depend both on temp. and pore diam., i.e. the thermodn. states of pore fluid and bulk fluid, but also strongly on the texture of the porous material. Pore condensation of argon can still be obsd. at 77 K, i.e. ∼6.5 K below the bulk triple point in MCM-48/-41 silica materials with pore diams. < 5 nm, but vanishes at this temp., when the pore diam. exceeds ∼12 nm (CPG). These observations indicate that the triple point of a fluid confined to silica pores is shifted to lower temp. compared to the bulk triple point. [on SciFinder(R)]
Keywords: pore condensation fluid mesoporous MCM silica glass